(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Agadatantra, a specialized branch of Ayurveda, focuses on the symptoms and management of poisons. Poisons are mainly classified into Sthavara and Jangama. Vrichika visha, a type of Keetavisha under Jangama visha, is known for its neurotoxic effects. The Ashtanga Hridaya Uttarasthana describes Hinguvadi Agada in the Keedaloothadi Visha Pratishedha Adhyaya as an effective formulation for managing Vrichika Visha. This simple herbomineral preparation includes Hingu, Haratala, and Matulunga and is administered in the form of Lepa and Anjana. Classical Ayurveda texts classify scorpions into three types based on the potency of their venom: Manda, Madya, and Mahavisha. While Lepa is effective for the local management of all three types of Vrichikadamsa, the Gutika-anjana form addresses systemic toxicity associated with Madya and Mahavisha types. The selection of ingredients in Hinguvadi Agada, especially Hingu and Matulunga, focuses on managing pain - a predominant symptom in scorpion stings. Acharya identified it as the best remedy for scorpion envenomation among the various available treatments due to its multidimensional pharmacological action. This article aims to explore the ingredients, preparation method, and probable pharmacological mechanisms of Hinguvadi Agada in neutralizing scorpion venom. Additionally, its possible applicability in managing other neurotoxic envenomations, such as cobra and krait bites, is discussed, highlighting its potential as a versatile antidotal yoga in Ayurvedic toxicology.